2021
DOI: 10.32604/phyton.2021.015871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Piriformospora indica on the Respiration of Taxus chinensis var. mairei under Water Stress

Abstract: Seedlings of Taxus chinensis var. mairei were used as experimental materials to study the adaptation of Piriformospora indica to this plant under water stress. The materials were divided into two groups, namely, with or without inoculation with P. indica. Each group was subjected to four different levels of water stress. Vitality and physiological and biochemical indexes of the roots of T. chinensis var. mairei were regularly measured. Under water stress, T. chinensis var. mairei had significantly decreased ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…It has been found that P. indica colonization increases vitamin C, protein, and soluble sugar content in cabbage, rapeseed, and cotton, and decreases nitrate levels to maintain higher plant metabolism under waterlogging [55]. In P. indica-inoculated host plants, root vitality and the enzyme activities on respiration and metabolism were significantly improved to withstand the hypoxic injury to plants under waterlogging stress [56]. Notably, the enzyme activity associated with reactive oxygen species (ROS) removal was significantly improved following the incubation of P. indica in rapeseed suffering from waterlogging [57].…”
Section: The Colonization Of P Indica Enhances Plant Tolerance To Wat...mentioning
confidence: 99%
“…It has been found that P. indica colonization increases vitamin C, protein, and soluble sugar content in cabbage, rapeseed, and cotton, and decreases nitrate levels to maintain higher plant metabolism under waterlogging [55]. In P. indica-inoculated host plants, root vitality and the enzyme activities on respiration and metabolism were significantly improved to withstand the hypoxic injury to plants under waterlogging stress [56]. Notably, the enzyme activity associated with reactive oxygen species (ROS) removal was significantly improved following the incubation of P. indica in rapeseed suffering from waterlogging [57].…”
Section: The Colonization Of P Indica Enhances Plant Tolerance To Wat...mentioning
confidence: 99%